Elevator model using MC68HC11 - Rayhana, Abd Walid (2009)
Lift or elevator is transport device that is used to move goods or people vertically. In this project, the MC68CHI I based lift control system is developed to simulate as a real elevator. There are two major modules which are microcontroller module and interface circuit module. Interface circuit module consists of dot-matrix, 7-segment, stepper motor, speech IC and buzzer. Dot-matrix and 7-segment are used as display mechanism to indicate the level floor while speech IC will notify the current position of elevator. It provides useful information to those who wish to carry out a lift control system research or project.